Case Study : Pak Tongko & Donut / Anis Farhana Sabri - Sabri, Anis Farhana (2021)
While I was doing the interview, I got to acknowledge the hardships and hurdles that an entrepreneur has to face in order for the business to be successful. Furthermore, I learned about entrepreneurial ventures on how to run a business using effective strategy and opportunities. The entrepreneur that I interviewed for my case study is Mohammad Juzaili bin Rahmani. He is the owner of Pak Tongko & Donut. He has a store that sells donuts and a Malaysian cuisine which is known as ‘cakoi’. Besides that, I acknowledge the fact that an entrepreneur must possess the Entrepreneurial Competencies for the business to run smoothly. The competencies can also encourage entrepreneurs to think various ways on how to overcome the obstacles in the business field. It astounded me how entrepreneurs could put those concepts into their daily life management. To simplify, as a student, it was my pleasure to learn about the business field management and the entrepreneur way of thinking into solving problems while managing the franchises successfully. I conclude that entrepreneurship is a space for the community to build connection amongst each other and acknowledge the self-improvement needed.